Natural Killer Cells for Cancer Immunotherapy: Pluripotent Stem Cells-Derived NK Cells as an Immunotherapeutic Perspective - Eguizabal, Cristina; Zenarruzabeitia, Olatz; Monge, Jorge; Santos, Silvia; Vesga, Miguel Angel; Maruri, Natalia; Arrieta, Arantza; Riñón, Marta; Tamayo-Orbegozo, Estibaliz; Amo, Laura; Larrucea, Susana; Borrego, Francisco (Frontiers in Immunology, 2014)
Natural killer (NK) cells play an essential role in the fight against tumor development. Over the last years, the progress made in the NK cell biology field and in deciphering how NK cell function is regulated, is driving efforts to utilize NK cell-based immunotherapy as a promising approach for the treatment of malignant diseases. Therapies involving NK cells may be accomplished by activating and expanding endogenous NK cells by means of cytokine treatment or by transferring exogenous cells by adoptive cell therapy and/or by hematopoietic stem cell transplantation (HSCT). NK cells that are suitable for adoptive cell therapy can be derived from different sources, including ex vivo expansion of autologous NK cells, unstimulated or expanded allogeneic NK cells from peripheral blood, derived from CD34+ hematopoietic progenitors from peripheral blood and umbilical cord blood, and NK cell lines. Besides, genetically modified NK cells expressing chimeric antigen receptors (CARs) or cytokines genes may also have a relevant future as therapeutic tools. Recently, it has been described the derivation of large numbers of functional and mature NK cells from pluripotent stem cells (PSCs), both embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), which adds another tool to the expanding NK cell-based cancer immunotherapy arsenal.